A Generic Decision Support Tool to Planning and Assignment Problems: Industrial Application & Industry 4.0 - Klement, Nathalie; Silva, Cristóvão; Gibaru, Olivier (Procedia manufacturing, 2017)
Decision support tools are essential to help the management of industrial systems at different levels: strategic to size the system; tactical to plan activities or assign resources; operational to schedule activities. We present a generic and modular decision support tool to solve different problems of planning, assignment, scheduling or lot-sizing. Our tool uses a hybridization between a metaheuristic and a list algorithm. The specification of the considered problem is considered into the list algorithm. Several tactical and operational problems have been solved with our tool: a problem of planning activities with resources assignment for hospital systems, a lot-sizing and scheduling problem taking into account the setup time for plastic injection, and a scheduling problem with precedence constraints. At the strategic level, this tool can also be used as part of the Industry 4.0 to design reconfigurable production systems. This paper summarizes some problems solved with the proposed tool, and presents the evolution of our tool.